Why are MoS2 monolayers not a good catalyst for the oxygen evolution reaction? - German, Estefania (2020)
We use density functional theory based calculations to study the energetics of the oxygen evolution reaction on a monolayer of MoS2. This material, a prototypical example of a layered transition metal dichalcogenide, is intensely studied in the context of many important catalytical applications, in particular for the hydrogen evolution reaction. The second half-reaction of the water-splitting process, the oxygen evolution reaction, is almost never considered on this material, due to its low activity. Based on our calculations, we explain this experimentally observed poor catalytic activity for the oxygen evolution by the weak binding of two key reaction intermediates (hydroxyl and hydroperoxyl) to the substrate. We explore substitutional doping with oxygen and phosphorous as means to facilitate the oxygen evolution on MoS2 layers. The oxygen substitution slightly increases the reaction´s overpotential, but does not significantly change the energetics. The doping with phosphorous, on the other hand, is not a promising way to promote the oxygen evolution on MoS2 layers. We also explore the role of the edges of MoS2 layers. We find that while the adsorption energies of reaction intermediates are strongly influenced by the presence of an edge, the final reaction overpotential remains nearly the same as on a pristine monolayer, meaning that the presence of edges is not favoring the OER.